2021
DOI: 10.17305/bjbms.2021.5876
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle and fiber type-specific intramyocellular lipid accumulation in obese mice

Abstract: In obesity, accumulation of lipid droplets in skeletal muscle fibers and a shift towards fast muscle fiber types can both contribute to insulin resistance. However, it is not yet clear how intramyocellular lipid accumulation and fiber type changes are associated. Therefore, we investigated to what extent the lipids accumulated in a fiber type-specific manner in the functionally similar fast-, intermediate- and slow‑twitch gastrocnemius, plantaris, and soleus muscles, respectively, in high-fat diet-induced obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 49 publications
1
14
0
1
Order By: Relevance
“…BODIPY staining of HFD muscles showed a prominent accumulation of intramyocellular lipids in two forms: intracellular microdroplets and sub-sarcolemmal plaques. Additionally, a recent study reported that lipid accumulation in HFD-fed mice was most prominent in type IIA and IIX fibers [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…BODIPY staining of HFD muscles showed a prominent accumulation of intramyocellular lipids in two forms: intracellular microdroplets and sub-sarcolemmal plaques. Additionally, a recent study reported that lipid accumulation in HFD-fed mice was most prominent in type IIA and IIX fibers [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that obese individuals have a decreased proportion of slow-twitch fibres and an increased proportion of fast-twitch fibres in skeletal muscles. 35 , 36 The genioglossus in patients with OSA have also been reported to have a higher proportion of fast-twitch fibres and be more vulnerable to fatigue. 37 In this study, we confirmed that a HFD caused significant changes in fibre types in the genioglossus, with the percentage of slow-twitch fibres declining and the percentage of fast-twitch fibres increasing.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical staining assay for MyHC isoforms was performed by the modified procedure, as described previously [41]. Briefly, QF muscles were collected and immediately fixed in 10% formalin.…”
Section: Myosin Heavy-chain Immunohistochemical Stainingmentioning
confidence: 99%